Perbandingan Kejadian Post-Operative Nausea And Vomitting Antara Puasa Dengan Tidak Puasa Pada Pasien Sectio Caesare Yang Dilakukan Regional Anestesi Di RSUD Caruban - Suhadi Suhadi; Sulastri Sulastri; Edi Santoso (Jurnal Ventilator, 2023)
ABSTRACT. Sectio Caesarea (SC) is a common and widely performed operation on pregnant women and its prevalence is increasing every year. The incidence of cesarean section in Indonesia is around 22.8% of all deliveries. Spinal anesthesia for cesarean section is very beneficial because of the simplicity of the technique, fast onset, reduced systemic toxicity but has the risk of complications that often occur after anesthesia and surgery are pain, nausea and vomiting. Objective: To analyze the comparison of the incidence of postoperative nausea and vomiting (PON-V) between fasting and non-fasting in patients with caesarean section who underwent regional anesthesia. Research Methods: Experimental research with clinical trials and including quantitative research. It will be held in March 2021 at IBS RSUD Caruban, Madiun Regency. The sampling technique was probability sampling using consecutive sampling where the sample consisted of 30 SC surgery patients who were divided into two groups, namely 15 fasting and non-fasting patients with spinal anesthesia. Data analysis using Paired Sample T Test with SPSS 22.00 for windows. Result : Post operative nausea and vomiting occurred in both groups . The difference in the incidence of PON-V in both fasting and non-fasting groups in cesarean section patients, the T test (independent T Test) showed a p value of 0.380 (p value > 0.05). Conclusion: There is no difference in the comparison of PON-V between fasting and non-fasting patients in sectio cesarean surgery patients at Caruban Hospital, Madiun Regency in 2021.